2011
DOI: 10.1002/cb.343
|View full text |Cite
|
Sign up to set email alerts
|

Brand names on packaging and their impact on purchase preference

Abstract: This study examines whether appearance of corporate, product and dual brand names (or a combination of brand names used together) on packaging influence consumer purchase preference. The face-to-face survey consists of consumers rating their purchase preference on a 7-point scale sixteen random brand names, and combinations of brand names on packaging along with three different prices, each for two product categories: chocolate and cereals -a total of 4032 observations are examined. Hypotheses are tested using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Other researchers have defined branding strategies at the company level by taking the entire portfolio of brands of the company as a unit of analysis which is discussed further. Corporate-dominant strategy is defined as the strategy in which only corporate brand name is used in all communications of the company (Gray and Smeltzer, 1985;Murphy, 1987;Laforet andSaunders, 1994, 2005). Olins (1989) has given it the name of Monolithic strategy whereas Aaker and Joachimsthaler (2000), and Rajagopal and Sanchez (2004) name it Branded House Strategy while Berens et al (2002) call it corporate branding strategy.…”
Section: Identifying Branding Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers have defined branding strategies at the company level by taking the entire portfolio of brands of the company as a unit of analysis which is discussed further. Corporate-dominant strategy is defined as the strategy in which only corporate brand name is used in all communications of the company (Gray and Smeltzer, 1985;Murphy, 1987;Laforet andSaunders, 1994, 2005). Olins (1989) has given it the name of Monolithic strategy whereas Aaker and Joachimsthaler (2000), and Rajagopal and Sanchez (2004) name it Branded House Strategy while Berens et al (2002) call it corporate branding strategy.…”
Section: Identifying Branding Strategiesmentioning
confidence: 99%
“…Olins (1989) has given it the name of Monolithic strategy whereas Aaker and Joachimsthaler (2000), and Rajagopal and Sanchez (2004) name it Branded House Strategy while Berens et al (2002) call it corporate branding strategy. Here, corporate brand symbolizes conglomerate name, company name and house/subsidiary name (Laforet andSaunders, 1994, 2005;Keller, 2008). Gray and Smeltzer (1985) also state that when a company, essentially operating in only one product line, uses its company brand only, it is called single entity branding strategy.…”
Section: Identifying Branding Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on branding has distinguished between different types of brands, for example Individual brands, Dual Brands and Corporate brands. In her study on chocolate and cereals, Laforet (2011) found that the purchase preferences were not influences by the type of brand, implying that it made no difference whether a brand was individual, dual or corporate. In fact, she found that both supermarkets' own labels and individual brands had a negative effect in the studied product categories.…”
Section: Introductionmentioning
confidence: 99%
“…I have previously also pointed out that some early works on the promotional role of packaging outside Nigeria include [4], [5], [6], [7]. Recent works and writings on the promotional role of packaging include [8], [9], [10], [11], [12], [13], [14], [15], [1, and 2]. [1,2] considered and empirically tested the packaging theory by [4], one of the outstanding theoretical works in the literature in assessing the effects of packaging on consumers.…”
Section: Introductionmentioning
confidence: 99%